Work Motivation: Peran Financial Incentive dan Non-Financial Incentive - Mariati Tirta Wiyata; Nuraeni Nuraeni; Bambang Somantri (Institut Manajemen Wiyata Indonesia, 2019)
This research was conducted at PT. Rismawan Pratama Bersinar, Sukabumi. In this study using two independent variables namely financial incentives as (X1) and non-financial incentives as (X2) and work motivation as the dependent variable (Y) which has the purpose of knowing: (1) the effect of financial incentives on employee work motivation, (2) the effect of non-financial incentives on employee work motivation, and (3) the effect of financial incentives and non-financial incentives on employee work motivation. The research method in this study is a survey method using a questionnaire distributed to all employees of PT. Rismawan Pratama Bersinar as research respondents totaling 63 people. Quality testing techniques used by researchers are by testing validity and reliability. For data analysis techniques using descriptive analysis, while to test the hypothesis the researcher uses multiple linear regression, partial test and simultaneous test. The results of the calculation of the data that has been processed using the SPSS 25 program shows that (1) financial incentives has a positive and significant effect on work motivation, (2) non-financial incentives has a negative and significant effect on work motivation, and (3) simultaneously financial and non-financial incentives have a positive and significant effect on the work motivation of employees of PT. Rismawan Pratama Bersinar, Sukabumi.